Efficient CRISPR Cas13 in The Treatment of The COVID-19 - Jian, Manli (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Currently, CRISPR Cas13 is one of the rapid advancement and growing potential in the fields of diagnostics and therapeutics. It has proven highly effective in detecting RNA viruses like SARS-CoV-2, making it an essential tool for identifying COVID-19 variants. However, since CRISPR Cas13 is a newly emerged technology in the CRISPR system, there are still some problems that need to be tackled. This article aims to discuss the application of CRISPR Cas13 in treating COVID 19. Two CRISPR Cas13 based diagnostic tools, PAC-MAN and CARMEN, hold potential for detecting variants, with research indicating their ability to degrade viral RNA and suppress viral gene expression. Despite this potential, challenges remain, particularly in achieving efficient and safe delivery systems for Cas13. While it is not yet fully implemented in clinical settings, the progress made so far highlights CRISPR Cas13’s significant role in addressing viral outbreaks, specifically COVID 19 and its potential for future applications in infectious diseases and other RNA-based conditions.